Placenta Accreta: A Spectrum of Predictable Risk, Diagnosis, and Morbidity - Duzyj, Christina M.; Cooper, Anne; Mhatre, Mohak; Han, Christina S.; Paidas, Michael J.; Illuzzi, Jessica L.; Sfakianaki, Anna K. (American Journal of Perinatology, 2019)
Objective Placenta accreta is a feared pathology, in part, because prenatal diagnosis is imperfect. It is not known whether clinical risk factors or sonographic features equally predict the entire graded pathological spectrum of placental overinvasion disease nor whether clinical outcomes differ along the spectrum.Study Design We conducted a mixed methods retrospective study of a cohort of women screened sonographically for placenta accreta, cross-referenced against cases identified by pathological diagnosis (N = 416). Demographic, diagnostic, and outcome information were compared across the spectrum of invasive placentation: percreta, increta, accreta, and focal accreta not requiring hysterectomy. The t-test, chi-square, Mann–Whitney, and Kruskal–Wallis tests were used for statistical analysis across groups.Results As the depth of invasion decreased, risk factors for placental overinvasion were less common, especially placenta previa and previous cesarean. There was also reduced anticipation by sonographic examination of the placenta. Rates of adverse outcomes were lower among women with focal accreta compared with those with deeper invasion.Conclusion As the depth of invasion decreases, clinical risk factors and sonographic evaluation are less reliable in the antenatal prediction of placenta accreta. The potential for unanticipated morbidity underscores the need for improved diagnostic tools for placenta accreta spectrum.
Keywords: placenta accreta; overinvasive placentation; placenta; retained placenta; ultrasound